Comparison of subjective well-being increasing strategies that Turkish and Swedish mothers use for their children - Baltacı, Kübra; Sapsağlam, Özkan (Southeast Asia Early Childhood Journal, 2021)
Education life begins in the family and parents are the first teachers of the children. Parenting attitudes are influenced by various variables like the parents' cultural characteristics. In this study, a comparison was made on subjective well-being increasing strategies used by Turkish-Swedish mothers for their children. It was aimed to examine the levels of subjective well-being increasing strategies implemented by Turkish and Swedish mothers for their children, to analyze the differences in terms of two subsamples, and to determine the determinants of the levels of subjective well-being increasing strategies implemented for children in the subsample and the total sample. The research was carried out using a quantitative descriptive scanning method and criterion sampling method. The sample of the study consists of 100 Turkish and 100 Swedish mothers who have children between the ages of 1 to 5.  In this study, the scale named ‘Subjective Well-Being Increasing Strategies Scale for Children (1-5 Ages)’ developed by Eryılmaz and Sapsağlam (2018) was used. The collection of the data is placed in two stages. The Swedish version of the scale was first implemented for Swedish mothers. For this, the Turkish version was first translated into English and then into Swedish for mothers. As a result of the findings, significant data were concluded that Turkish mothers implemented higher level subjective well-being increasing strategies for their children. When the average values were examined, it was concluded that mothers who did not work implemented higher level subjective well-being increasing strategies for their children than working mothers. Besides this, the mothers who have high school and lower level implemented higher level subjective well-being increasing strategies for their children. In line with the results of the research, it can be said that culture is effective in the well-being of increasing strategies that mothers use for their children.